Forecasting Average Daily Temperature in the Khorasan Razavi Province - sayyed mohamad Hosseini; Abdolhossein Adelzadeh (تحقیقات کاربردی علوم جغرافیایی)
In this research, applied synoptic model for determining the average daily temperature and its relationship with the Geopotential Height in middle level (500 HPa). Therefore, two database were used: database of atmospheric circulations, includes the data of geopotential height at 500 HPa and its data were extracted from the NCEP/DOE(US National Oceanic and Atmospheric Administration) in hours 00:00; 03:00; 06:00; 09:00; 12:00; 15:00; 18:00; and 21:00 in Zulu and other, database of environmental (surface) events. Contain of average daily temperature in the Mashhad, Torbat-Heydarieh and Sabzevar stations in Khorasan Razavi Province. The maximum and minimum of these stations in the time interval from 01/01/1987 to 01/01/2014 equal as 9862 days from the meteorological organization of Iran. Then, was calculated the correlation of the average daily temperature of selected stations with high atmospheric data (500 HPa level) with the northern hemisphere in Surfer Software. The result shown, four regions in the northern hemisphere which had high correlations with selected stations. The correlation results suggest that the United States has 25 pixels, Northern China 25 pixels, Africa 45 pixels and Japan with 65 pixels. Then, weighted average of pixels in heights by multiple regression equation station. The results of diagnostic models indicate that, per geopotential height increase in the profile, the average daily temperatures of selected stations in the Sabzevar 1.4, Torbat-Heydarieh 1.3 and Mashhad 1.3 degrees Celsius will increase.